Perception of the Mogao Caves’ Art Heritage in Republican China (1911–1949): From Obscurity to National Treasure - Merekina, Olga O.; Panova, Olga S. (Actual Problems of Theory and History of Art, 2022)
This paper examines the history of the re-discovery of the Mogao murals and how the public’s perception of their artistic value changed over the course of the first half of the 20th century. The analysis of primary sources shows that the evolution of that perception coincided with the shift in the understanding of art, national identity, and history in China. The cave-temple complex of Mogao in Dunhuang (Gansu province, China) contains more than a thousand cliffside caves which were excavated and decorated between the 4th and 14th centuries C.E. The murals and sculptures in these caves demonstrate a unique multicultural exchange that took place along the Silk Road trade routes for a millennium. By the beginning of the 20th century, the Mogao complex had fallen into neglect. In 1899, the Daoist monk Wang Yuanlu discovered a “library-cave” with thousands of manuscripts and fragments of paintings. The encounter of Chinese intellectuals with manuscripts from the library cave in the 1900s launched the beginning of the Dunhuang studies, which for the next few decades remained highly text-oriented. After the Qing empire fell in 1911, the public associated the Mogao complex primarily with the looting of cultural relics by “foreign imperialists.” It was only towards the end of the 1930s that the intellectuals of Republican China became interested in the murals. This interest grew into a series of expeditions led by Chinese artists and archaeologists. Multiple exhibitions of copies of the murals introduced the art of Dunhuang to the Chinese public, and by the time of the establishment of the People’s Republic of China in 1949, they had become a national cultural symbol.
Keywords: Dunhuang; Mogao complex; preservation of cultural heritage; mural painting; copying; Chen Wanli; Zhang Daqian; Chang Shuhong; Wang Ziyun